PUBLIC ADMINISTRATION AND ORGANIZATION THEORY an annotated bibliography. - Acharya, Tulasi; Traille, Kay (ROUTLEDGE, 2025)
The book surveys crucial theories and practices and academic research in the field of public administration and Organizational theory. It outlines ground breaking findings and arising from quality research works from the past to the present--especially focused on articles that are both timely and contextual. Each chapter opens with a theme, explains its relevance within the context and presents a critical annotated bibliography of the articles under the theme and provides a thematic conclusion of the chapter. This book will be a valuable resource for teachers, researchers and students in the field of public administration.
Keywords: Public administration -- Bibliography.; elektronické knihy; electronic books